2012
DOI: 10.1136/bmj.e8105
|View full text |Cite
|
Sign up to set email alerts
|

Mind wandering and driving: responsibility case-control study

Abstract: Objective To assess the association between mind wandering (thinking unrelated to the task at hand) and the risk of being responsible for a motor vehicle crash.Design Responsibility case-control study.Setting Adult emergency department of a university hospital in France, April 2010 to August 2011.Participants 955 drivers injured in a motor vehicle crash.Main outcome measures Responsibility for the crash, mind wandering, external distraction, negative affect, alcohol use, psychotropic drug use, and sleep depriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
108
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 17 publications
3
108
0
2
Order By: Relevance
“…Subjects 4,7,13) and less in others (e.g. Subjects 5,6). Also, we observe that the correlation related features (Feature Set 2) do not increase the detection efficiency when used in combination with Feature Set 1, and also result in lower results when used alone.…”
Section: Subject Independent Cognitive Load Detectionmentioning
confidence: 57%
See 1 more Smart Citation
“…Subjects 4,7,13) and less in others (e.g. Subjects 5,6). Also, we observe that the correlation related features (Feature Set 2) do not increase the detection efficiency when used in combination with Feature Set 1, and also result in lower results when used alone.…”
Section: Subject Independent Cognitive Load Detectionmentioning
confidence: 57%
“…Many studies show that driver distraction is one of the most important causes of traffic accidents, along with alcohol use and speeding. A study conducted in France showed that 17% of 453 accidents that resulted in admittance to the emergency room was caused by a high mental distraction of the responsible driver [6]. More recent studies from the same group has shown that induced distractive thoughts led to less micro-regulation of both speed and lateral position and narrowed visual scanning of the driving scene [7], that mind wandering is the cause of 8% of close to 1000 accidents according to emergency room interviews with the drivers [8] and that it affects 85.2% of the drivers especially in situations requiring less attention from the driver such as an everyday commute or a monotonous motorway [9].…”
mentioning
confidence: 99%
“…Authors from France stated that their two observational epidemiological studies were the first to assess the risk of RTC related to driver's distraction in the Emergency Departments. They found that distraction caused 8 to 17% of RTCs 11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Thinking deeply beyond the driving task will distract the driver and increase the risk of RTCs. An observational study has shown that more than half of the drivers who had a RTC had some degree of mind wandering before collisions 12 . Similar to our study, a survey from Sweden showed that 3.2% of drivers who were involved with RTC's were distracted by deep thinking 16 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of research investigating the concept of MW, suggesting potential causes that could foster such a phenomenon. Only one epidemiological study has focused on this issue in a critical driving context (Galéra et al, 2012), and it revealed the harmful effects of MW in increasing the risk of a car crash. Experimental studies rather consider that driver would adduce in MW (Lemercier et al, 2014).…”
mentioning
confidence: 99%